Personal Software Process with Automatic Requirements Traceability to Support Startups - Jirapanthong, Waraporn (Journal of Reviews on Global Economics, 2017)
This paper applies Personal Software Process (PSP) for software development activities, and uses PSP scripts to follow the activities in software development. In particular, we have adapted a development script in order to enable automatic traceability. The script is the cyclical process that is designed for developing a large program in a sequence of small incremental steps. Moreover, we have extended an XTraQue tool to enable an automatic traceability during using PSP. This enables the completeness of traceability during using PSP. The Part-of-Speech (POS) embedded XML-based templates of software artefacts for PSP-based development, that is, functional requirements (FR), use case, and class diagram are defined. We perform an explanatory case study in order to evaluate the effectiveness between manual and automatic traceability during the personal software process (PSP). In particular, the causal links between software artefacts created during software development are so-called traceability relations. The result evaluation are concerned with precision and recall measures on the creation of traceability relations.